Pola Asuh Orang Tua Terhadap Motivasi Belajar Siswa SMP Unggulan ‘Aisyiyah Bantul - Saibah Saibah; Wantini Wantini (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2021)
The first and main institution is the family, who provides early knowledge, guidance, attention and affection that they feel is very influential in the process of psychological growth and even social development in children. Parenting by parents greatly influences the success of a child. The purpose of this study is to find out the factors that influence the low motivation of student learning and to find out how the parenting of students at home, so influence children’s learning motivation. This type of research is descriptive with a qualititave approach. Research subjects are students and home room teachers. Data collected in this study used interview and observation techniques. The data collected is analyzed using interactive analysis of miles and huberman which covering 3 data reduction, data display and conclusion drawing or verification. The results showed that the learning facilities of parents have an effect but are meaningless without good assistance from parents. In the educational environment the influence of peers, teachers and class atmosphere is also a supporting factor in increasing student motivation. Keywords: Parenting; Motivation to Learn; Supporting Factor